Effect of Edible oil on Lipid metabolism and Expressions of Scavenger Receptor Class-B Type 1 in Rabbit Liver - Ahamed, Syed Nasir; Venkateswarulu, T.C.; Rahamathulla, Syed (Indian Journal of Animal Nutrition, 2022)
Â To investigate the effect of Edible Oil on HDL and scavenger receptor class-B type 1 in rabbit liver. SR-B1 is extremely expressed in various tissues, including the liver, where its pronouncement is modulated by different mechanisms, which includes the transcriptional activity of nuclear receptors. Eighteen albino rabbits were fed with rabbit food pallets for 21 days, of which 06 were selected as normal diet (Group-I), and the other 06 were fed with Edible oil diet 2ml/Kg + feed (Group-II) and third group 06 Rabbits were fed with edible oil diet 5ml/Kg + feed (Group-III). Estimation of HDL levels in serum and the expression levels of scavenger receptor class-B type 1 genes in rabbit liver were determined by using real-time fluorescent quantitative PCR, ELISA and Western blot. However the expressions of SR-B1 mRNAs, protein levels and SR-B1activity Â in Group-II and group - III were over expression significantly as compared with those in Group-I. Low elevation of HDL levels are observed in serum of Group -III compared with Group-II and Group-I. Conclusion: Edible oil showed consequently regulative effect on liver by a potential mechanism of overexpression SR-B1 genes, protein abundance, activity of SR-B1 and low concentrations of high density lipoprotein (HDL) in serum, accordingly holding down the cholesterol synthesis in rabbit liver.